Voting behaviour in Malaysia: locating the sociological determinants of ethnicity, middle classes and development gains - Mohd Noor, Mansor (IDOSI Publications, 2016)
Studying voting behavioural demands scholars to have a good grasp of the changing conceptual and theoretical frameworks as the societal changes are very dynamic. This study focuses on the changing voting patterns in a plural society of Malaysia in which ethnicity dominated the election outcome. Since the election in 2004 results at the state and national levels show that the concern for development agenda by the middle clasess across ethnic divide has redefined the political landscape. This study shows that development agenda could transform a plural society that ensured a flowering of democratic culture in the nation.